Factors influencing solution in karren and on covered karst - Veress, Márton (Hungarian Geographical Bulletin, 2010)
The effect of the following factors on karstifi cation were investigated: the presence of Pinus mugo, slope length, and slope angle (Totes Gebirge, Austria), the wind action (Diego de Almagro Island, Chile), the thickness and quality of covering sedimentary rock (Bakony Mountains, Mecsek Mountains, Hungary) and the role of karst water (tsingies, Madagascar). The methods were as follows. The specific cross-sectional area of rinnenkarren and their specific shape-parameter in Totes Gebirge were calculated. Morphological maps of several karren forms at Diego de Almagro Island were prepared and specific width of these karren features was also computed. Topographic cross-sections were created and height measurements of Madagascar tsingy areas carried out as well. Vertical electrical sounding (VES) method was applied in the Bakony Mountains and in the Mecsek Mountains. The following conclusions could be established: dissolution is more intense on slopes with Pinus mugo than on bare slopes. Rinnenkarren (channels) may develop under rivulets, but they can be created by seepage, too. The wind moves the water on Diego de Almagro Island, therefore it controls the dissolution process. On the windward side of landforms both the number and the size of karren forms are increased and as a result, the amount of total dissolution is also higher due to the wind effect. Tsingies represent the initial phase of karstification. They develop when the karst water table sinks temporarily to a lower level after reaching the surface. The covered karst forms of the Bakony Mountains developed at places where the covering sedimentary rocks are thinner, whereas the covered karst features in the Mecsek Mountains developed where the clay beds of the covering sedimentary strata end.